Variety of size and form of GRM2 bacterial microcompartment particles - Cesle, Eva Emilija; Filimonenko, Anatolij; Tars, Kaspars; Kalnins, Gints (Protein science, 2021)
Bacterial microcompartments (BMCs) are bacterial organelles involved in enzymatic processes, such as carbon fixation, choline, ethanolamine and propanediol degradation, and others. Formed of a semi-permeable protein shell and an enzymatic core, they can enhance enzyme performance and protect the cell from harmful intermediates. With the ability to encapsulate non-native enzymes, BMCs show high potential for applied use. For this goal, a detailed look into shell form variability is significant to predict shell adaptability. Here we present four novel 3D cryo-EM maps of recombinant Klebsiella pneumoniae GRM2 BMC shell particles with the resolution in range of 9 to 22 Å and nine novel 2D classes corresponding to discrete BMC shell forms. These structures reveal icosahedral, elongated, oblate, multi-layered and polyhedral traits of BMCs, indicating considerable variation in size and form as well as adaptability during shell formation processes.
Keywords: bakteriální proteiny; Bacterial Proteins; elektronová kryomikroskopie; Klebsiella pneumoniae; Cryoelectron Microscopy